Active Compounds, Antioxidant Potential, and Formulation Innovations of Oxalis sp.: A Bibliometric Perspective - Fitri Kurniasari; Anita Sukmawati; Andi Suhendi (Jurnal Kefarmasian Indonesia, 2026)
The genus Oxalis, belonging to the family Oxalidaceae R.Br., comprises approximately 504 recognized species that are widely distributed worldwide, particularly in regions ranging from South America to southern North America, as well as in the southwestern Cape region of South Africa. In Egypt, this genus is represented by five species and one variety, namely Oxalis anthelmintica A. Rich., O. corniculata L., O. corniculata var. repens (Thunb.) Zucc., O. corymbosa DC., O. latifolia Kunth, and O. pes-caprae L. However, information on the isolation and characterization of non-polar and volatile constituents from Oxalis species remains limited. Therefore, this study applied bibliometric analysis to evaluate the development of research on Oxalis sp., particularly regarding antioxidant activity, formulation development, and phytochemical studies. Data were obtained from the Crossref database, resulting in 57 selected articles published between 2015 and 2025. Bibliometric analysis was conducted using VOSviewer to map publication trends, keyword co-occurrence networks, overlay visualization, and influential articles related to Oxalis research. A total of 214 publications from 2015–2025 were analyzed. The results show that 22 keywords were grouped into four clusters, forming 154 links with a total link strength of 962, indicating a well-connected research structure. The dominant research themes focus on antioxidant activity, antibacterial activity, and secondary metabolites, particularly in studies on Oxalis corniculata. However, keywords related to formulation development and advanced phytochemical analysis appear less frequently, suggesting that these areas remain relatively underexplored. These findings provide a systematic overview of the research landscape and highlight potential directions for future studies on the development and application of Oxalis-derived bioactive compounds.